BRAND TRUST MEDIATING THE EFFECTS OF SOCIAL MEDIA MARKETING, INFLUENCER CREDIBILITY, AND ONLINE REVIEWS ON PURCHASE INTENTION - Zulfadli Zulfadli; Tibrani Tibrani; Rona Tanjung; Surya Kusumah; Mohd Asmadi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study examines the effects of influencer credibility and online customer reviews on purchase intention through the mediating role of brand trust in social commerce. A quantitative approach was employed using survey data collected from 200 respondents in Batam, Indonesia, who actively engage in social commerce and have experience with influencer-based purchases and online reviews. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that both influencer credibility and online customer reviews significantly influence brand trust, with online customer reviews exerting a stronger effect. Brand trust, in turn, has a significant positive impact on purchase intention and serves as a key mediating mechanism between the independent variables and purchase intention. Although influencer credibility and online customer reviews also directly affect purchase intention, their indirect effects through brand trust are stronger. These results suggest that trust plays a crucial role in converting digital engagement into purchase intention. The study contributes to the social commerce literature and provides practical implications for marketers seeking to develop credible and trust-oriented digital marketing strategies. Keywords : Influencer Credibility, Online Customer Reviews, Brand Trust, Purchase Intention